Preparation method of temperature-regulating Lyocell fiber loaded with phase-change microcapsules

By preparing small-particle-size phase-changing microcapsules in Lyocell fibers and dispersing them uniformly in NMMO solution, the problems of phase-changing microcapsules loss and insufficient fiber flexibility are solved, and the preparation of Lyocell fibers with high enthalpy and good temperature regulation capabilities are achieved. .

CN119265724APending Publication Date: 2025-01-07WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371353.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the existing preparation methods for phase change temperature-regulating fibers, phase change microcapsules are easily lost during use, resulting in a decrease in the temperature regulation ability of the fibers and poor flexibility of textiles.

Method used

The phase change microcapsules were prepared by reacting styrene maleic anhydride copolymer with sodium hydroxide, adjusting the pH of the emulsifier to 4-5, forming an oil-in-water emulsion, and reacting with melamine formaldehyde prepolymer, and then uniformly in NMMO solution. Dispersed, and Lyocell fibers loaded with phase change microcapsules were prepared by wet spinning.

Benefits of technology

The prepared fibers have small diameters, high enthalpy heat and good temperature regulation capabilities, while increasing the flexibility of textiles, improving the stability of phase-change microcapsules and the comfort of fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067663410000071
    Figure BDA0005067663410000071
  • Figure BDA0005067663410000072
    Figure BDA0005067663410000072
  • Figure BDA0005067663410000081
    Figure BDA0005067663410000081
Patent Text Reader

Abstract

The invention discloses a preparation method of temperature-adjusting Lyocell fibers loaded with phase change microcapsules, and belongs to the technical field of phase change materials. The method comprises the following steps: 1) reacting SMA with a sodium hydroxide solution, and adjusting the pH value with a citric acid solution to obtain an emulsifier, wherein the SMA accounts for 4-6% of the total mass of the emulsifier; carrying out high-speed shearing emulsification on an emulsifier and n-octadecane for 20-40 minutes to form an oil-in-water emulsion, dropwise adding the melamino-formaldehyde prepolymer under mechanical stirring, and reacting to obtain a phase change microcapsule; and 2) uniformly dispersing the phase change microcapsules into 45-55wt% of an NMMO aqueous solution, then removing water to increase the concentration of the NMMO to 80-90%, then sequentially adding propyl gallate and wood pulp powder, and after the wood pulp powder is completely dissolved, carrying out wet spinning to obtain the phase change microcapsule loaded temperature-regulating Lyocell fiber. The obtained fiber is small in diameter, has high enthalpy heat and good temperature adjusting capability, and is wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase change materials, and in particular relates to a method for preparing a temperature-regulating Lyocell fiber loaded with phase change microcapsules. Background Art

[0002] With the increasing depletion of non-renewable energy, the development of new energy with high energy utilization has become one of the current research hotspots. Phase change materials can absorb or release heat through reversible changes between their own phases within a certain temperature range, thus having the ability to control temperature and realizing the role of two-way temperature regulation. Phase change materials are not only green and environmentally friendly, but also inexpensive, and are expected to become one of the new energy-saving and environmentally friendly materials with application value. Phase change thermostatic fiber is a kind of intelligent fiber that combines phase change material with fiber in a certain way. When the ambient temperature changes, the phase change material absorbs or releases heat through its own phase change to keep the fiber temperature constant. Fabrics made of phase change thermostatic fiber can keep the internal ambient temperature stable and meet the human body's requirements for comfort.

[0003] Lyocell fiber is known as the green fiber of the 21st century. It is a regenerated cellulose fiber that is wet-spun using N-methylmorpholine-N-oxide (NMMO) as a solvent. The NMMO solvent used in production is green and environmentally friendly, and can be recycled, refined and reused. The entire production system forms a closed-loop recycling system with no waste discharge and no pollution to the environment. It realizes the clean production of regenerated cellulose fiber and is recognized as a "man-made green fiber". Lyocell fiber has higher strength, weaker shrinkage and better thermal stability than natural cellulose and viscose fibers. Temperature-regulating Lyocell fiber is prepared using phase change materials, which can store and release huge latent heat during isothermal phase change. However, the preparation method of phase change thermostatic fiber is mostly to spray phase change microcapsules on the surface of the fiber, thereby increasing the loss of phase change microcapsules during the use of phase change thermostatic fiber. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for preparing temperature-regulating Lyocell fibers loaded with phase change microcapsules. The obtained fibers have a small diameter, which is beneficial to increasing the softness of the textiles made later, and also have high enthalpy heat and good temperature regulation capabilities.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] Provided is a method for preparing a temperature-adjustable Lyocell fiber loaded with phase change microcapsules, comprising the following steps:

[0007] 1) After reacting styrene maleic anhydride copolymer (SMA) with sodium hydroxide solution, the pH of the reaction solution is adjusted to 4-5 with citric acid solution to prepare an emulsifier, wherein SMA accounts for 4-6% of the total mass of the emulsifier; then the emulsifier and n-octadecane are uniformly dispersed by ultrasonication, and high-speed shear emulsification is performed at a speed of 8000-10000 rpm for 20-40 minutes to form an oil-in-water emulsion, and finally melamine formaldehyde prepolymer is added dropwise under mechanical stirring to prepare phase change microcapsules by reaction;

[0008] 2) The phase change microcapsules prepared in step 1) are uniformly dispersed in an NMMO aqueous solution, wherein the NMMO concentration in the NMMO aqueous solution is 45-55wt%; then, water is removed at a temperature of 90-100°C to raise the NMMO concentration to 80-90%, and then propyl gallate and wood pulp powder are added in sequence. After the wood pulp powder is completely dissolved, wet spinning is performed to obtain a temperature-adjustable Lyocell fiber loaded with phase change microcapsules.

[0009] According to the above scheme, in step 1), the mass ratio of styrene maleic anhydride copolymer (SMA) to sodium hydroxide is 2 to 3:1.

[0010] According to the above scheme, in step 1), the concentration of the sodium hydroxide solution is 2-3 wt%.

[0011] According to the above scheme, in step 1), the concentration of the citric acid solution is 18-25%.

[0012] According to the above scheme, in step 1), the reaction temperature of styrene maleic anhydride copolymer (SMA) and sodium hydroxide is 80-90° C., and the reaction time is 3-4 hours.

[0013] According to the above scheme, in step 1), the ultrasonic dispersion time of the emulsifier and n-octadecane is 10 to 20 minutes.

[0014] According to the above scheme, in the step 1), the emulsifier and n-octadecane are emulsified at a temperature of 70-80° C. to form an oil-in-water emulsion.

[0015] According to the above scheme, in step 1), the reaction is carried out at 70-80° C. for 3-4 hours to prepare phase change microcapsules.

[0016] According to the above scheme, in step 1), the mass ratio of n-octadecane to emulsifier is 1:3-4.

[0017] According to the above scheme, in step 1), the mechanical stirring speed is 350-400 rpm.

[0018] According to the above scheme, in step 1), the prepared phase change microcapsules are washed twice with deionized water, then washed twice with 50-70% anhydrous ethanol, and dried at a temperature of 50-60°C.

[0019] According to the above scheme, in step 1), melamine, formaldehyde solution and deionized water are mixed, stirred and reacted at 70-80° C. for 1-2 hours, heating is stopped when the solution becomes clear, and the pH value of the solution is adjusted with triethanolamine to obtain a melamine formaldehyde prepolymer.

[0020] Preferably, the pH value of the solution is adjusted to 8-9 with triethanolamine.

[0021] Preferably, the concentration of the formaldehyde solution is 36-38%.

[0022] According to the above scheme, in step 1), the particle size of the phase change microcapsules obtained is 2 to 3 um.

[0023] According to the above scheme, in step 2), water is removed at a temperature of 90-100° C. so that the NMMO concentration is increased to 80-90%, and the main method is: vacuum pumping.

[0024] According to the above scheme, in step 2), the mass ratio of the 45-55wt% NMMO aqueous solution to the total mass of the phase change microcapsules and the wood pulp powder is 15-16:1.

[0025] According to the above scheme, in step 2), the mass ratio of wood pulp powder to phase change microcapsules is 8-9:1; propyl gallate accounts for 0.08-0.09wt% of the mass of the wood pulp powder.

[0026] According to the above scheme, in step 2), wet spinning is to prepare a spinning solution, extrude it through a spinneret to form fibers, and then condense the fibers.

[0027] According to the above scheme, in step 2), the diameter of the obtained temperature-regulating fiber is 8 to 9 um.

[0028] The present invention provides a temperature-regulating fiber. First, phase-change microcapsules with a smaller particle size are prepared. Then, the phase-change microcapsules with a smaller particle size and wood pulp powder are uniformly and stably dispersed in NMMO to obtain a temperature-regulating and humidity-regulating fiber with a smaller diameter. While ensuring a good mixing temperature, the textile made of the fiber is more compliant, effectively increasing the comfort of the skin contacting the fiber. The specific preparation process is as follows:

[0029] When preparing phase change microcapsules, the present invention first directly adjusts the pH of the emulsifier to 4-5 when configuring the emulsifier. On the one hand, it avoids the occurrence of a large amount of foam during the emulsification process and the viscosity after emulsification, which increases the difficulty of pH control of the obtained oil-in-water emulsion; on the other hand, it is also conducive to obtaining a stable oil-in-water emulsion. Combined with the appropriate concentration of SMA in the emulsifier, the shear rate and emulsification time when the emulsifier is emulsified with n-octadecane, the obtained oil-in-water emulsion and melamine formaldehyde prepolymer are obtained to obtain uniformly dispersed small-particle phase change microcapsules, wherein the capsule wall is melamine formaldehyde prepolymer and the capsule core is n-octadecane. The uniformly dispersed small-particle phase change microcapsules provide a basis for the subsequent preparation of temperature-regulating fibers with smaller diameters.

[0030] The present invention adds small-size phase change microcapsules into a 45-55wt% low-concentration NMMO aqueous solution, which is beneficial to the uniform dispersion of the small-size phase change microcapsules in the NMMO solvent, and then increases the concentration of the NMMO aqueous solution to 70-80% by removing water, which is beneficial to the full dissolution of wood pulp powder. Propyl gallate is used as a stabilizer, which is beneficial to the slurry being in a stable state at high temperature and in a closed container, and finally realizing the preparation of fibers with smaller diameters through wet spinning.

[0031] The beneficial effects of the present invention are as follows:

[0032] The invention provides a method for preparing temperature-regulating fibers. The method comprises the following steps: adjusting the pH value of an emulsifier, controlling the appropriate concentration of SMA, the shear rate and the emulsification time of the emulsifier and n-octadecane in advance, obtaining a stable oil-in-water emulsion, and reacting the emulsifier with a melamine formaldehyde prepolymer to obtain uniformly dispersed small-particle phase-change microcapsules; then, using a low-concentration NMMO aqueous solution to uniformly disperse the phase-change microcapsules, increasing the concentration of the NMMO aqueous solution to fully dissolve wood pulp powder, and using the stabilizing effect of propyl gallate to smoothly prepare fibers with smaller diameters through wet spinning; the method has a simple preparation process, and the obtained fibers not only have smaller diameters, which is beneficial for increasing the softness of textiles made later, but also have high enthalpy and good temperature regulation capabilities. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The scanning electron microscope (SEM) images of the phase change microcapsules prepared in Example 1 and Comparative Examples 2 and 3 of the present invention are shown in FIG. Figure 1 b is MEPCM-2 obtained in Example 1, Figure 1 a is MEPCM-1 obtained in Comparative Example 2, Figure 1 c is the MEPCM-3 obtained in Comparative Example 3.

[0034] Figure 2 The differential scanning calorimetry (DSC) endothermic peak curves of the phase change microcapsules prepared with different emulsifier contents in Example 1 of the present invention and Comparative Examples 2 and 3 are shown.

[0035] Figure 3 Differential scanning calorimetry (DSC) exothermic peak curves of phase change microcapsules prepared with different emulsifier contents in Example 1 and Comparative Examples 2 and 3 of the present invention.

[0036] Figure 4 This is a scanning electron microscope (SEM) image of the fiber (Lyocell-1) prepared in Comparative Example 1 of the present invention.

[0037] Figure 5 This is a scanning electron microscope (SEM) image of the loaded phase change microcapsule fiber (Lyocell-2) prepared in Example 1 of the present invention.

[0038] Figure 6 The differential scanning calorimetry (DSC) endothermic peak curves of the fibers (Lyocell-1 and Lyocell-2) prepared in Comparative Example 1 and Example 1 of the present invention.

[0039] Figure 7 The differential scanning calorimetry (DSC) exothermic peak curves of the fibers (Lyocell-1 and Lyocell-2) prepared in Comparative Example 1 and Example 1 of the present invention. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0041] Example 1

[0042] A method for preparing a temperature-regulating fiber of a Lyocell fiber loaded with phase-change microcapsules comprises the following steps:

[0043] 1) Preparation of phase change microcapsules

[0044] S1. 10 g of styrene maleic anhydride copolymer (SMA) was added to 154 g of an aqueous solution containing 4 g of sodium hydroxide at a temperature of 85 ° C. The reaction time was 3 h. The solution was mixed evenly and the heating was stopped. The pH value of the reaction solution was adjusted to 4.43 with a citric acid solution prepared with 7.5 g of citric acid and 28.5 g of deionized water to obtain an emulsifier having a mass percentage of SMA in the solution of about 5%;

[0045] S2. 2.5 g of melamine and 5.5 g of 37% formaldehyde solution were measured, and the molar ratio of the two materials was about 1:2. The melamine and formaldehyde were added to a beaker, and 12 ml of deionized water was added. The mixture was stirred at 75° C. for 2 h. When the solution became clear, heating was stopped. The pH value of the solution was adjusted to 8-9 with a 20% triethanolamine aqueous solution to obtain a melamine formaldehyde prepolymer.

[0046] S3. Take 36g of the emulsifier prepared in step S1 and 12g of n-octadecane and add them to a beaker, the mass ratio of the two materials is 3:1, and ultrasonicate for 10 minutes to obtain a uniformly dispersed solution. The temperature is 75°C, and emulsify for 30 minutes at a speed of 10,000 rpm using a high-speed shearing machine to form an oil-in-water emulsion. Take a small amount of the emulsion with a glass rod and observe its morphological characteristics under a microscope. The emulsion is uniformly spherical under the microscope.

[0047] S4. The oil-in-water emulsion prepared in step S3 is mechanically stirred at a speed of 400 rpm, and the melamine formaldehyde prepolymer prepared in step S2 is added dropwise to the oil-in-water emulsion at a temperature of 75° C. and reacted for 4 h;

[0048] S5. The prepared phase change microcapsules were washed twice with deionized water, and then washed twice with 50% anhydrous ethanol, and dried at a temperature of 50°C to finally obtain phase change microcapsules, named MEPCM-2.

[0049] 2) Preparation of temperature-regulating fibers of Lyocell fibers loaded with phase change microcapsules by wet spinning

[0050] S1. 1150 g of 50 wt% NMMO solvent and 8 g of the phase change microcapsules MEPCM-2 prepared in step 1) were added to the reactor, the temperature was adjusted to 100 ° C, and vacuum pumped for about 1 h to make the NMMO solvent content reach about 85 wt%;

[0051] S2. 0.06 g of propyl gallate and 67 g of wood pulp powder were added to the NMMO solvent in sequence and stirred for 1 h to obtain a phase change microcapsule / cellulose solution; a sample was taken and observed under a microscope. No fiber fragments were found, indicating that the wood pulp powder was completely dissolved in the NMMO solvent; nitrogen was introduced and the material was discharged under pressure for 30 min to remove the waste;

[0052] S3. The phase change microcapsule / cellulose solution obtained in S2 is sent to a filtration device for filtration, the filtration size of the filtration device is 15μm, and then spinning is carried out. The fibers ejected from the spinneret are passed through a coagulation bath and are wound in a three-roller machine to prepare fibers. The prepared fibers are then washed with water three times and dried in an oven for 12 hours at a temperature of 50°C to obtain temperature-regulated Lyocell fibers loaded with phase change microcapsules, named Lyocell-2; wherein in Lyocell-2, the phase change microcapsules account for 12% of the mass of the wood pulp powder.

[0053] Comparative Example 1

[0054] A method for preparing wet-spun fibers comprises the following steps:

[0055] S1. 1150 g of 50 wt% NMMO solvent was added to the reactor of the homemade spinning apparatus, the temperature was adjusted to 100 ° C, and vacuum pumping was performed for about 1 hour to make the NMMO solvent content reach about 85 wt%;

[0056] S2. 0.06 g of propyl gallate and 67 g of wood pulp powder were added to the NMMO solvent in sequence and stirred for 1 h to obtain a cellulose solution; a sample was taken and observed under a microscope. No fiber fragments were found, indicating that the wood pulp powder was completely dissolved in the NMMO solvent; nitrogen was introduced and the material was discharged under pressure for 30 min to remove waste;

[0057] S3. The cellulose solution obtained in S2 is sent to a filtration device for filtration. The filtration size of the filtration device is 15 μm. Then spinning is carried out. The fibers ejected from the spinneret are passed through a coagulation bath and wound in a three-roller machine to prepare fibers. The prepared fibers are then washed with water three times and dried in an oven at 50°C for 12 hours to prepare Lyocell fibers, which are named Lyocell-1.

[0058] Comparative Example 2

[0059] 1) Preparation of phase change microcapsules

[0060] S1. 8 g of styrene maleic anhydride copolymer (SMA) was added to 150 g of an aqueous solution containing 4 g of sodium hydroxide (NaOH), the temperature was 85 ° C, the reaction time was 3 h, the solution was mixed evenly, the heating was stopped, and the pH value of the solution was adjusted to 4.52 with 7.5 g of citric acid and 30.5 g of deionized water to an emulsifier with a mass ratio of SMA in the solution of about 4%;

[0061] S2. 2.5 g of melamine and 5.5 g of 37% formaldehyde solution were measured, and the molar ratio of the two materials was about 1:2. The melamine and formaldehyde were added to a beaker, and 12 ml of deionized water was added. The mixture was stirred at 75° C. for 2 h. When the solution became clear, heating was stopped. The pH value of the solution was adjusted to 8-9 with a 20% triethanolamine aqueous solution to obtain a melamine formaldehyde prepolymer.

[0062] S3. Take 36g of the 4wt% emulsifier prepared in step (S1) and 12g of n-octadecane, add them to a beaker, the mass ratio of the two materials is 3:1, ultrasonicate for 10min to obtain a uniformly dispersed solution, the temperature is 75°C, use a high-speed shearing machine at a speed of 10000rpm, emulsify for 30min to form an oil-in-water emulsion, take a small amount of the emulsion with a glass rod and observe its morphology under a microscope;

[0063] S4. The oil-in-water emulsion prepared in step (S3) is mechanically stirred at a speed of 400 rpm, and the melamine formaldehyde prepolymer prepared in step (S2) is added dropwise to the oil-in-water emulsion at a temperature of 75° C. and reacted for 4 h;

[0064] S5. The prepared phase change microcapsules were washed twice with deionized water, and then washed twice with 50% anhydrous ethanol, and dried at a temperature of 50° C. Finally, phase change microcapsules were obtained, named MEPCM-1.

[0065] 2) Preparation of thermoregulatory fibers by wet spinning

[0066] The fiber was prepared by referring to the process of Example 1, but the particle size of the phase change microcapsules prepared in this comparative example was too large (see Figure 1 a), and the diameter of the spinneret of the spinning machine is 9um, so during the spinning process, the spinneret will be blocked, thereby affecting the amount of filaments output from the spinneret. When all the spinnerets are blocked, the spinning will be interrupted.

[0067] Comparative Example 3

[0068] 1) Preparation of phase change microcapsules

[0069] S1. 12 g of styrene maleic anhydride copolymer (SMA) was added to 150 g of an aqueous solution containing 4 g of sodium hydroxide (NaOH), the temperature was 85 ° C, the reaction time was 3 h, the solution was mixed evenly, heating was stopped, and the pH value of the solution was adjusted to 4.38 with 7.5 g of citric acid and 26.5 g of deionized water to obtain an emulsifier with a mass ratio of SMA in the solution of about 6%;

[0070] S2. 2.5 g of melamine and 5.5 g of 37% formaldehyde solution were measured, and the molar ratio of the two materials was about 1:2. The melamine and formaldehyde were added to a beaker, and 12 ml of deionized water was added. The mixture was stirred at 75° C. for 2 h. When the solution became clear, heating was stopped. The pH value of the solution was adjusted to 8-9 with a 20% triethanolamine aqueous solution to obtain a melamine formaldehyde prepolymer.

[0071] S3. Take 36g of the emulsifier with a content of 6wt% prepared in step (S1) and 12g of n-octadecane, add them to a beaker, the mass ratio of the two materials is 3:1, ultrasonicate for 10min to obtain a uniformly dispersed solution, the temperature is 75°C, use a high-speed shearing machine at a speed of 10000rpm, emulsify for 30min to form an oil-in-water emulsion, take a small amount of the emulsion with a glass rod and observe its morphology under a microscope;

[0072] S4. The oil-in-water emulsion prepared in step (S3) is mechanically stirred at a speed of 400 rpm, and the melamine formaldehyde prepolymer prepared in step (S2) is added dropwise to the oil-in-water emulsion at a temperature of 75° C. and reacted for 4 h;

[0073] S5. The prepared phase change microcapsules were washed twice with deionized water, and then washed twice with 50% anhydrous ethanol, and dried at a temperature of 50°C to finally obtain phase change microcapsules, named MEPCM-3.

[0074] 2) Preparation of thermoregulatory fibers by wet spinning

[0075] The fiber was prepared by referring to the process of Example 1, but the phase change microcapsules prepared in this comparative example were agglomerated (see Figure 1 c) The diameter of the spinneret of the spinning machine is 9um, so during the spinning process, the spinneret will be blocked, thereby affecting the amount of filaments output from the spinneret. When all the spinnerets are blocked, the spinning will be interrupted and spinning cannot be carried out, and no fiber can be obtained.

[0076] Figure 1 The phase change microcapsules MEPCM-1 ( Figure 1 a) MEPCM-2( Figure 1 b) and MEPCM-3(( Figure 1 c) Scanning electron microscope (SEM) images; Figure 1 a shows that the particle size of MEPCM-1 is larger. Figure 1 c shows that the particle size of MEPCM-3 is small, but agglomeration occurs. Figure 1b shows that the particle size of MEPCM-2 is uniform and has a diameter of about 3um. Since the diameter of the spinneret of the spinning machine is 9um, when the diameter of the phase change microcapsules is too large or agglomerated, the spinneret will be blocked, affecting the spinning efficiency. When all the spinnerets are blocked, the spinning will be interrupted and no fiber can be obtained.

[0077] Figure 2 , 3 The differential scanning calorimetry (DSC) endothermic peak curves and exothermic peak curves of phase change microcapsules prepared with different emulsifier contents are respectively prepared in Example 1 of the present invention and Comparative Examples 2 and 3.

[0078]

[0079] The figure and table show that as the proportion of the emulsifier increases, the melting enthalpy and crystallization enthalpy of the phase change microcapsule increase, and the coverage rate also increases, thereby increasing the utilization of the phase change material.

[0080]

[0081] Figure 4 This is a scanning electron microscope (SEM) image of the fiber (Lyocell-1) prepared in Comparative Example 1 of the present invention; the image shows that the fiber surface is relatively smooth.

[0082] Figure 5 This is a scanning electron microscope (SEM) image of the phase change microcapsule-loaded fiber (Lyocell-2) prepared in Example 1 of the present invention; the image shows that the fiber surface is relatively rough, with uneven spherical small particles evenly dispersed on the surface of the fiber, proving that the phase change microcapsules are doped in the fiber.

[0083] Figure 6 , 7 The differential scanning calorimetry (DSC) endothermic peak curve and exothermic peak curve of the fibers (Lyocell-1 and Lyocell-2) prepared in Comparative Example 1 and Example 1 of the present invention; the following data can be obtained according to the figure.

[0084]

[0085] The figure shows that when the diameter of the fiber is 9um and the proportion of the phase change microcapsules is 12% of the fiber, the melting enthalpy and crystallization enthalpy of the prepared lyocell fiber loaded with phase change microcapsules are 12.1 and 14.5 (J / g), respectively. The capsules have a higher enthalpy heat, which is beneficial to temperature regulation.

[0086] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method for preparing a temperature-adjustable Lyocell fiber loaded with phase change microcapsules, characterized in that: The following steps are involved: 1) After reacting styrene maleic anhydride copolymer with sodium hydroxide solution, the pH of the reaction solution is adjusted to 4-5 with citric acid solution to prepare an emulsifier, wherein SMA accounts for 4-6% of the total mass of the emulsifier; then the emulsifier and n-octadecane are uniformly dispersed by ultrasonication, and high-speed shear emulsification is performed at a speed of 8000-10000 rpm for 20-40 minutes to form an oil-in-water emulsion, and finally melamine formaldehyde prepolymer is added dropwise under mechanical stirring to react and prepare phase change microcapsules; 2) The phase change microcapsules prepared in step 1) are uniformly dispersed in an NMMO aqueous solution, wherein the NMMO concentration in the NMMO aqueous solution is 45-55wt%; then, water is removed at a temperature of 90-100°C to raise the NMMO concentration to 80-90%, and then propyl gallate and wood pulp powder are added in sequence. After the wood pulp powder is completely dissolved, wet spinning is performed to obtain a temperature-adjustable Lyocell fiber loaded with phase change microcapsules.

2. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of the styrene maleic anhydride copolymer to the sodium hydroxide is 2 to 3:

1.

3. The preparation method according to claim 1, characterized in that: In the step 1), the concentration of the sodium hydroxide solution is 2-3 wt %; the concentration of the citric acid solution is 18-25 %.

4. The preparation method according to claim 1, characterized in that: In the step 1), the reaction temperature of the styrene maleic anhydride copolymer and sodium hydroxide is 80-90° C., and the reaction time is 3-4 hours.

5. The preparation method according to claim 1, characterized in that: In the step 1), the emulsifier and n-octadecane are emulsified at a temperature of 70-80° C. to form an oil-in-water emulsion.

6. The preparation method according to claim 1, characterized in that: In the step 1), the reaction is carried out at 70-80° C. for 3-4 hours to prepare phase change microcapsules.

7. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of n-octadecane to the emulsifier is 1:3-4.

8. The preparation method according to claim 1, characterized in that: In the step 1), melamine, formaldehyde solution and deionized water are mixed, stirred and reacted at 70-80° C. for 1-2 hours, heating is stopped when the solution becomes clear, and the pH value of the solution is adjusted with triethanolamine to obtain a melamine formaldehyde prepolymer.

9. The preparation method according to claim 1, characterized in that: In the step 2), the mass ratio of 45-55wt% NMMO aqueous solution to the total mass of phase change microcapsules and wood pulp powder is 15-16:1; the mass ratio of wood pulp powder to phase change microcapsules is 8-9:1; and propyl gallate accounts for 0.08-0.09wt% of the mass of wood pulp powder.

10. The preparation method according to claim 1, characterized in that: In the step 1), the particle size of the obtained phase change microcapsules is 2 to 3 um; in the step 2), the diameter of the obtained temperature regulating fibers is 8 to 9 um.